Improving changeover time: a tailored SMED approach for welding cells - Guzmán, Ferradás P; Salonitis, Konstantinos (Elsevier, 2013)
Short changeover times have always been critical in manufacturing business. Set-up duration reduction initiatives have been associated with Shingós ‘Single Minute Exchange of Die' (SMED) method. Although a great number of companies have initiated SMED, some failed on implementation. The main reason is that strict application of Shingós SMED methodology is not the most efficient way to reduce set-up times in all situations. In the present study a tailored methodology is presented that has been developed specifically for an automotive supplier. The validation of the proposed method was done through implementation on an industrial welding cell for a period of four months. The main finding is that in addition to SMED tailored methodology, appropriate strategy definition and preparatory activities are key enablers for success. That includes project targets and timescale definition, selection of the appropriate team and coordinator, allocation of specific roles and responsibilities to each team member, training of team and shop floor staff on the new methodology and changeover standards. By implementing the new tailored SMED improvement programme, the company achieved 33% reduction on changeover time.
Keywords: Lean manufacturing; SMED; Changeover time; Set-up time